Social, Casual and Mobile Games The Changing Gaming Landscape - Willson, Michele; Leaver, Tama (Bloomsbury Academic, 2016)
This book is available as open access through the Bloomsbury Open Access programme and is available on www.bloomsburycollections.com. Social, casual and mobile games, played on devices such as smartphones, tablets, or PCs and accessed through online social networks, have become extremely popular, and are changing the ways in which games are designed, understood, and played. These games have sparked a revolution as more people from a broader demographic than ever play games, shifting the stereotype of gaming away from that of hardcore, dedicated play to that of activities that fit into everyday life. Social, Casual and Mobile Games explores the rapidly changing gaming landscape and discusses the ludic, methodological, theoretical, economic, social and cultural challenges that these changes invoke. With chapters discussing locative games, the new freemium economic model, and gamer demographics, as well as close studies of specific games (including Candy Crush Saga, Angry Birds, and Ingress), this collection offers an insight into the changing nature of games and the impact that mobile media is having upon individuals and societies around the world.